Programming microcontrollers in C - Van Sickle, Ted. (Embedded technology series., 2001)
Ted Van Sickle spent over fifteen years at Motorola as a microcontroller specialist. He now consults and teaches classes on software design and programming for microcontroller systems. He holds a MSEE from the University of Michigan.